2022
DOI: 10.3390/v14061247
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SARS-CoV-2 Evasion: Interferon Pathway and Therapeutic Options

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is responsible for the current COVID-19 pandemic. SARS-CoV-2 is characterized by an important capacity to circumvent the innate immune response. The early interferon (IFN) response is necessary to establish a robust antiviral state. However, this response is weak and delayed in COVID-19 patients, along with massive pro-inflammatory cytokine production. This dysregulated innate immune response contributes to pathogenicity and in some individuals leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 147 publications
2
21
0
Order By: Relevance
“…DVGs from RSV and influenza can function as primary triggers to directly stimulate type I IFN production through RIG-I like receptors (Sun and López 2017). It is previously reported that SARS-CoV-2 RNAs can be recognized by MDA5 (Thorne, Reuschl et al 2021, Znaidia, Demeret et al 2022) and we showed that the expression of MDA5 (IFIH1) was elevated in DVG+ cells at 2 dpi (Fig. 6C).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…DVGs from RSV and influenza can function as primary triggers to directly stimulate type I IFN production through RIG-I like receptors (Sun and López 2017). It is previously reported that SARS-CoV-2 RNAs can be recognized by MDA5 (Thorne, Reuschl et al 2021, Znaidia, Demeret et al 2022) and we showed that the expression of MDA5 (IFIH1) was elevated in DVG+ cells at 2 dpi (Fig. 6C).…”
Section: Discussionsupporting
confidence: 69%
“…Alternatively, if DVGs do not directly stimulate IFN production, they can suppress the expression of viral-encoding IFN antagonists by large deletions, resulting in an earlier and higher IFN expression in DVG+ cells. Indeed, IFN antagonists are encoded in NSP1, NSP3, NSP5, NSP12, NSP13, NSP14, NSP15, ORF3a, ORF3b, ORF6, ORF7a, ORF7b, ORF8, ORF9b, N, and M (Lei, Dong et al 2020, Xia, Cao et al 2020, Han, Zhuang et al 2021, Wong, Cheung et al 2022, Znaidia, Demeret et al 2022) and most of them are within the deletion regions based on our conserved genomic hotspots for DVG recombination sites (Fig. 2A and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…ORF9b also blocks the TLR3-TRIF pathway [ 135 ]. Nearly all the SARS-CoV-2 proteins have been suggested to block IFN production and signaling at various points in the IFN pathway, and this has been extensively characterized [ 136 ]. Aside from blocking TLR and RLR signaling specifically, ORF6 prevents nuclear localization of the transcription factor signal transducer and activator of transcription 1 (STAT1), which is needed for IFN production [ 137 ].…”
Section: Ifn Signaling In Covid-19 Pathogenesismentioning
confidence: 99%
“…A decrease in IFN-promoter activity mediated by MAVS. TRIM59 [10] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ORF3b 1. Restricting the nuclear translocation of IRF3.…”
Section: Introductionmentioning
confidence: 99%